A mathematical programming model for high school timetabling problem (2016)
This paper presents a mathematical programing model that supports the design of timetables of classes in primary and secondary educational institutions, allowing the decision maker to take into account the constraints and variables that are commonly associated to this problem. Our model diers from most of those in the literature as the objective function aims at maximizing the number of blocks, two consecutive hours of lecture devoted to the same subject, which favors the learning process, optimizes teachers' agendas by reducing idle times and reduces cost and contractual diculties.  The model is validated using a real instance of a middle size institution for which the current timetable is considerably improved. Additionally, computational experiments with larger instances were carried on in order to test the capacity of the model for which promising results were obtained.